2015
DOI: 10.1021/acs.jpcc.5b08089
|View full text |Cite
|
Sign up to set email alerts
|

Raman Scattering from a Molecule–Semiconductor Interface Tuned by an Electric Field: Density Functional Theory Approach

Abstract: Spectroscopic chemical characterization of atomic-scale interfaces is a challenging scientific problem. In the search for new spectroscopic capabilities, we investigate nonresonant Raman interactions that occur at the interface between organic adsorbates and inorganic surfaces. Our system is a trans-1,2-bis(4-pyridyl)ethylene molecule adsorbed to a semiconductor PbSe surface. We employ first-principles density functional methods to investigate the vibrational dynamics and Raman spectra of this absorbate−surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
21
1
Order By: Relevance
“…[9] This enhanced vibrational coupling significantly increased the ICTP and thus magnified the Raman signals.Based on the above findings,we believe optimization of the morphology geometry and promotion of the ICTP between the semiconductor and molecules are two effective approaches for EF enhancement in semiconductor SERS.S pecially,t he ICTP depends on the distribution of electron cloud density on the surface of semiconductor substrates. [15,16] Generally,t he highly ordered periodic lattices of crystalline semiconductor materials would enhance the constraint to the electrons. [17] In contrast, the long-range disordered structure of amorphous materials can cause dangling bonds and band tails,w hich could lead the energy of the system to am etastable state [17][18][19] and thus facilitate the surface electron escape and transfer.Motivated by these exciting findings,w ed eveloped an ovel semiconductor nanomaterial for competitive SERS technology,that is,amorphous ZnO nanocages (a-ZnO NCs).…”
mentioning
confidence: 99%
“…[9] This enhanced vibrational coupling significantly increased the ICTP and thus magnified the Raman signals.Based on the above findings,we believe optimization of the morphology geometry and promotion of the ICTP between the semiconductor and molecules are two effective approaches for EF enhancement in semiconductor SERS.S pecially,t he ICTP depends on the distribution of electron cloud density on the surface of semiconductor substrates. [15,16] Generally,t he highly ordered periodic lattices of crystalline semiconductor materials would enhance the constraint to the electrons. [17] In contrast, the long-range disordered structure of amorphous materials can cause dangling bonds and band tails,w hich could lead the energy of the system to am etastable state [17][18][19] and thus facilitate the surface electron escape and transfer.Motivated by these exciting findings,w ed eveloped an ovel semiconductor nanomaterial for competitive SERS technology,that is,amorphous ZnO nanocages (a-ZnO NCs).…”
mentioning
confidence: 99%
“…Several theoretical models have been developed to study SERS activity of semiconductor nanostructures . For example, it has been reported that the optical resonance of surface complex can greatly increase the Raman cross section .…”
mentioning
confidence: 99%
“…Also, the photoinduced charge transfer process in semiconductor‐molecule system can effectively lead to larger molecular polarization tensor . Furthermore, the facet‐dependent SERS has been predicted by density functional theory calculations, where facets have significant impact on the interfacial charge transfer process between molecules and semiconductor substrates . However, the convincing experimental evidences for facet‐dependent SERS are still missing due to the complexity of physical and chemical properties of semiconductor surfaces.…”
mentioning
confidence: 99%
See 2 more Smart Citations